Rice cultivar tolerance to preemergence- and postemergence-applied fluridone - Maria C.C.R. Souza; Jason K. Norsworthy; Pâmela Carvalho-Moore; Amar Godar; Samuel B. Fernandes; Thomas R. Butts (Weed Technology, 2025)
Fluridone was registered for use in rice production in 2023, offering a new herbicide site of action for growers. However, little information is available on the degree of rice tolerance to this herbicide. Field experiments conducted in 2022 and replicated in 2023 near Colt, AR, evaluated the tolerance of 12 rice cultivars to fluridone, applied preemergence or at the 3-leaf growth stage, in separate experiments. Each experiment consisted of one cultivar. Fluridone rates included 0, 168 (1 × label rate), and 336 (2 × label rate) g ai ha−1 in all experiments. Visible injury varied between years in all experiments, likely due to different environmental conditions. In 2022, injury following preemergence applications of fluridone was below 25% across cultivars. In contrast, in 2023, injury ≥30% occurred to five cultivars, with a maximum of 58% observed for the cultivar ‘DG263L’. In both years, only three cultivars exhibited injury ≥20% following fluridone applications at the 3-leaf stage. Fluridone negatively affected shoot density, groundcover, chlorophyll content, and days to 50% heading in most cultivars when applied preemergence. When fluridone was applied to 3-leaf rice, at least one of the variables evaluated was negatively affected in two and nine cultivars in 2022 and 2023, respectively. Grain yield reductions of at least 18% were observed from eight cultivars in 2022, and a grain yield decrease from 9% to 49% from eight cultivars occurred in 2023 in the preemergence experiments. Fluridone applied to rice at the 3-leaf stage did not cause a yield penalty to any cultivar in 2022, whereas in 2023, a yield loss occurred from eight cultivars. Yield loss from the DG263L cultivar occurred at the 1 × rate in both experiments, indicating that this cultivar appears to be sensitive to fluridone, regardless of the application timing. Based on these findings, fluridone tolerance is cultivar-dependent. Furthermore, preemergence applications of fluridone to rice should be avoided.